Chromosome abnormalities and genetic counseling - Gardner, R. J. McKinlay; Sutherland, Grant R (Oxford University Press, 2004)
Genetic Health Services Victoria and Murdoch Children\'s Institute, Melbourne, Australia. Discusses genetic counseling and how to help concerned parents make informed decisions. Covers the basics of genetics, parents with chromosomal abnormality, and prenatal diagnosis. Previous edition: c1996.
Oxford monographs on medical genetics ; no. 46
Keywords: Chromosome Disorders; vrozené vady; Genetic Diseases, Inborn; chromozomální aberace; Congenital Abnormalities; Chromosome Aberrations; genetika, lékařská genetika; Genetic Counseling; chromozomální poruchy; genetické poradenství; genetické nemoci vrozené